Correlations of Plasma Thyroxine with Activated Partial Thromboplastin Time and Fibrinogen Levels in Hyperthyroid Patients - Ayesha Imtiaz Malik, Farheen Zehra, Ayesha Shafqat, Saima Tabassum, Najma Qureshi, Nida Tosif (Pakistan Journal of Medical & Health Sciences, 2022)
Background: A complex pattern of hypercoagulability is associated with hyperthyroidism which is attributed to the actions mediated by boosting up of platelet activation, release of pro-coagulatory cytokines and chemokines, and probable interactions of activated platelets and endothelial cells that may lead to increased risk for intravascular thrombosis. Hyperthyroidism is linked to higher levels of fibrinogen, vWF and factor VIII, lower levels of plasminogen and plasminogen activator, decrease in PT and activated partial thromboplastin time (aPTT) levels and non-significant changes in PAI and antiplasmin levels. Aim: To assess the hypercoagulability and determine the correlation of plasma T4 with aPTT and fibrinogen levels in hyperthyroid patients. Methods: It was an observational prospective study carried out at Niazi Medical College and teaching hospital, Sargodha from January to November 2021. 118 patients with diagnosed hyperthyroidism and above 15 years were recruited in the study that did not have history of coagulability of blood such as hemophilia, immune disorders, cancers, pregnancy, clinically known hypercoagulable state, and on any type of anticoagulant therapy. Levels of thyroid hormones (TSH, T3 and T4), aPTT and fibrinogen were measured in the laboratory. Data was analyzed using SPSS version 20. Frequencies, percentages and range were calculated for categorical variables. Spearman’s correlation was used to determine the correlation between plasma T4 levels and aPTT and plasma T4 and fibrinogen in all patients. Results: Cumulative results showed that 34 (29%) patients had T4 level between 11– 16µg/dl, 45(38%) between 17- 21µg/dl and 39(33%) had T4 levels > 21 µg/dl. Spearman’s correlation’s results to determine association between plasma T4 and aPTT revealed that a strong negative correlation (rs= -.67, p< .001) exists between plasma levels of Thyroxine (M = 18.49, SD= 3.78) and aPTT (M=23.70, SD=1.70). A moderate positive correlation (rs= .37, p < .001) is evident between plasma thyroxine (M = 18.49, SD = 3.78) and fibrinogen (M = 4.27, SD = 0.43) levels. Conclusion: High levels of thyroxine (T4) lead to a hypercoagulable state due to shortened aPTT and higher fibrinogen levels and there is a strong negative correlation between plasma thyroxine (T4) and aPTT and fibrinogen levels in hyperthyroid patients.